2022
DOI: 10.1038/s41598-022-07457-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and related comorbidities on the risks of developing tinnitus

Abstract: This is a retrospective longitudinal study that uses data from the National Health Insurance Research Database (NHIRD) of Taiwan of which hypothyroid patients who received a diagnosis between 2000 and 2010 were selected and followed up until 2011. The primary outcome of this study was the occurrence of tinnitus (ICD-9-CM code 388.3). The relevant comorbidities were selected as potential confounders according to the literature, which included vertigo (ICD-9-CM code 386), insomnia (ICD-9-CM code 780), anxiety (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Likewise, Tricarico et al [27] speculated that patients with hypothyroidism have an increased risk of recurrent BPPV, which is particularly high in hypothyroid patients with positive thyroid antibodies, suggesting an association between autoimmunity and recurrent vertigo. In addition, our observation is similar to the study by Hsu et al [38], who demonstrated a relationship between hypothyroidism and tinnitus, another symptom encountered in vestibular pathologies such as Menière's disease. These authors found that patients with hypothyroidism displayed an increased risk of developing tinnitus.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Tricarico et al [27] speculated that patients with hypothyroidism have an increased risk of recurrent BPPV, which is particularly high in hypothyroid patients with positive thyroid antibodies, suggesting an association between autoimmunity and recurrent vertigo. In addition, our observation is similar to the study by Hsu et al [38], who demonstrated a relationship between hypothyroidism and tinnitus, another symptom encountered in vestibular pathologies such as Menière's disease. These authors found that patients with hypothyroidism displayed an increased risk of developing tinnitus.…”
Section: Discussionsupporting
confidence: 92%
“…Research indicates that hypothyroidism decreases heart contractility, reduces stroke volume and rate, affects the vascular endothelium, and increases the risk of atherosclerosis, systemic vascular resistance, hypertension [1]. atherogenic lipid profile, and coagulation abnormality [2].…”
Section: Introductionmentioning
confidence: 99%